2019
DOI: 10.1186/s12888-019-2372-4
|View full text |Cite
|
Sign up to set email alerts
|

Moral cognition, the missing link between psychotic symptoms and acts of violence: a cross-sectional national forensic cohort study

Abstract: BackgroundPeople with schizophrenia are ten times more likely to commit homicide than a member of the general population. The relationship between symptoms of schizophrenia and acts of violence is unclear. There has also been limited research on what determines the seriousness and form of violence, such as reactive or instrumental violence. Moral cognition may play a paradoxical role in acts of violence for people with schizophrenia. Thoughts which have moral content arising from psychotic symptoms may be a ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 81 publications
1
10
0
1
Order By: Relevance
“…The authors concluded that little is known about a) how to provide effective treatment or reduce the risk of assault carried out by these prolific, high risk patients and b) little is known about their motivations for carrying out the assaults which in some cases may be instrumental rather than expressive e.g. patients wishing to separate from other patients and staff due to a belief that that they will be harmed [ 8 ], or because of moralistic attitudes or cognitions [ 9 , 10 ]. Or reactive violence related to impaired neurocognition and social cognition [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that little is known about a) how to provide effective treatment or reduce the risk of assault carried out by these prolific, high risk patients and b) little is known about their motivations for carrying out the assaults which in some cases may be instrumental rather than expressive e.g. patients wishing to separate from other patients and staff due to a belief that that they will be harmed [ 8 ], or because of moralistic attitudes or cognitions [ 9 , 10 ]. Or reactive violence related to impaired neurocognition and social cognition [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with schizophrenia are, in general, not violent. However, there is an increase in violent behavior in schizophrenia [ 1 ], and with violent offenses [ 2 ], in particular, homicide [ 3 , 4 , 5 ]. A study has reported that the five-year incidence of violent conviction after first being diagnosed with schizophrenia was 11% in men and 3% in women [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Repetitive violence is often a multifactorial construct that involves biological, psychosocial, emotional, and pathophysiological factors and contextual, environmental, family-oriented, and situational features, alone or in combination [ 10 , 11 , 12 , 13 , 14 ]. Disorder-specific determinants, such as psychotic symptoms, are not always the sole factor involved in violence [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations